Effective Horsepower Predictions for United States Coast Guard Proposed Icebreaker Design Represented by Model 5169. - Day, William G., Jr (1968)
This report presents the results of bare hull resistance tests on one model which represents a candidate hull form for a proposed U. S. Coast Guard medium polar icebreaker. This model has the same form forward of station 7. The tests were oriented toward choice of an optimum afterbody shape. (Author)